Empirical antimicrobial therapy for late-onset sepsis in a neonatal unit with high prevalence of coagulase-negative Staphylococcus - Roberta Maia de Castro Romanelli; Lêni Márcia Anchieta; Ana Carolina Bueno e Silva; Lenize Adriana de Jesus; Viviane Rosado; Wanessa Trindade Clemente
Abstract Objective: The aim of this study was to compare two different empiric treatments for late-onset neonatal sepsis, vancomycin and oxacillin, in a neonatal intensive care unit with a high prevalence of coagulase-negative Staphylococcus. Methods: A cross-sectional study was conducted in an neonatal intensive care unit from 2011 to 2014. Data from the medical records of at-risk newborns were collected daily. Infections were defined according to the National Health Surveillance Agency criteria. Data analysis was performed using an internal program. Results: There was a significant reduction in the number of Staphylococcus aureus infections (p = 0.008), without endocarditis, meningitis, or lower respiratory tract infection, as well as a reduction in the frequency of deaths related to S. aureus infection. There were no significant changes in the incidence of Gram-negative bacterial or fungal infections. An increase in coagulase-negative Staphylococcus infections was observed (p = 0.022). However, there was no measured increase in related morbidity and mortality. There was a reduction in the median number of days of treatment with oxacillin from 11.5 to 6 days (p < 0.001) and an increase of one day in the median number of days of treatment with vancomycin (p = 0.046). Conclusions: Modification of the empiric treatment regimen for neonatal late-onset sepsis with use of oxacillin showed a significant reduction in S. aureus infections, as well as a reduction in the frequency of infections with major organ system involvement and mortality due to infection with this microorganism. As a result, oxacillin can be considered as an effective treatment for late-onset sepsis, making it possible to avoid broad-spectrum antibiotics.